The Geographic Information System applied to study schistosomiasis in Pernambuco - Verônica Santos Barbosa; Rodrigo Moraes Loyo; Ricardo José de Paula Souza e Guimarães; Constança Simões Barbosa (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Diagnose risk environments for schistosomiasis in coastal localities of Pernambuco using geoprocessing techniques. METHODS A coproscopic and malacological survey were carried out in the Forte Orange and Serrambi areas. Environmental variables (temperature, salinity, pH, total dissolved solids and water fecal coliform dosage) were collected from Biomphalaria breeding sites or foci. The spatial analysis was performed using ArcGis 10.1 software, applying the kernel estimator, elevation map, and distance map. RESULTS In Forte Orange, 4.3% of the population had S. mansoni and were found two B. glabrata and 26 B. straminea breeding sites. The breeding sites had temperatures of 25ºC to 41ºC, pH of 6.9 to 11.1, total dissolved solids between 148 and 661, and salinity of 1,000 d. In Serrambi, 4.4% of the population had S. mansoni and were found seven B. straminea and seven B. glabrata breeding sites. Breeding sites had temperatures of 24ºC to 36ºC, pH of 7.1 to 9.8, total dissolved solids between 116 and 855, and salinity of 1,000 d. The kernel estimator shows the clusters of positive patients and foci of Biomphalaria, and the digital elevation map indicates areas of rainwater concentration. The distance map shows the proximity of the snail foci with schools and health facilities. CONCLUSIONS Geoprocessing techniques prove to be a competent tool for locating and scaling the risk areas for schistosomiasis, and can subsidize the health services control actions.